Design Of A Layer-Layed Security System For Jewelry Vaults Utilizing A Time-Based One-Time Password (Otp) Algorithm Using Fingerprint And Microcontroller-Based Telegram - Wira Adtiya; Hadi Syahputra; Nanda Tommy Wirawan (Journal of Computer Scine and Information Technology, 2024)
On campus, the security of student and employee belongings is crucial. Currently, the security system for safes still relies on manual locks or card keys, which are vulnerable to theft and fraud. Therefore, the development of a more sophisticated and secure security system is necessary. One solution is to utilize the Time-Based One Time Password (OTP) algorithm to strengthen locker security. The OTP algorithm generates a unique password each time a user opens the locker, making it more difficult for unauthorized parties to access. Furthermore, the use of fingerprint technology and Telegram as a medium for sending OTP codes can also enhance system security. Fingerprints are used to identify authorized users, while Telegram is used to send OTP codes to users. This tool is processed with an Arduino Mega 2560 microcontroller as a connection.